A crônica numa abordagem multimodal - Rosalice Aparecida Entreportes (2015)
The final conclusion work results of applying an educational project carried out with a group of 22 students of the 9th grade of elementary school to a public school of the state of Minas Gerais, in the reading area. The central objective of the project is to promote reading development, through chronic genre, considering the multimodality of language. Anchored in theories of reading as interaction, the genre as a work tool in school and multimodality to provide the multiliteracies, we analyze the application of the results through the notes, daily observations , resolution of the activities carried out by participating students, the chronic retextualization selected and the assessment made by the students of chronic design a multimodal approach involving reading, with emphasis on the importance on reading strategies and semiotic resources for reading comprehension.